INOVASI WATERPROOFING COATING CEMENT BASED DENGAN PEMANFAATAN LIMBAH STYROFOAM - Jati, Ninggar Syifa Nur; Salsabila, Ranatri Diani; Susanti, Riza; Hartono, Hartono (BANGUNAN, 2023)
One of them is the porous structure, which triggers the loss of construction strength and causes the building structure to become brittle, so that a leak-proof or waterproof coating is needed to prevent water from penetrating into the building structure. In the market, waterproofing prices are relatively high, starting at one hundred thousand per kilogram, so waterproofing innovations are needed at affordable prices. The purpose of this research is to create a method for implementing and testing waterproofing coatings derived from a mixture of Styrofoam and additives, identify technical and physical data for waterproofing mixtures derived from test results, and analyze the best type of mixture of Styrofoam and additives for waterproofing. This study used styrofoam waste dissolved in thinner, which has the final property of water resistance, with added waterglass as an adhesive and shell waste and fly ash as cementitious solid additives. The research method used was experimental, with four variations of waterproofing mixtures using fly ash and clam shells added. Tests carried out based on SNI 8665:2018 in-packaging test, ASTM D1640 Touch dry and hard dry time test, ASTM D3359 pull-off adhesion test, SNI 0096:2007 Water permeability test, ASTM D471 water absorption test, ASTM D4798 Weather resistance test, and SNI 8665:2018 Spreadability test The results showed that of the 4 mixed variants, the optimum mixture was obtained in variation C with a ratio of 4:1:5 for dissolved styrofoam, waterglass, and dense fly ash added material. This mixture meets all the test criteria at a more affordable price than on the market. So by utilizing this waste for waterproofing, it is hoped that it can reduce Styrofoam waste, which is difficult to decompose and abundant in Indonesia, and meet the needs of the waterproofing market.